2001
DOI: 10.1002/1099-0682(20011)2001:1<267::aid-ejic267>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

New Alkyl−Cobalt(III) Complexes with Tridentate Amino−Oxime Ligands: Synthesis, Structure, and Reactivity

Abstract: The oxidative addition of alkyl halides to the Co I species generated by the reduction of [Co III (LNHpy)(HLNHpy)]-(ClO 4 ) 2 (1), where HLNHpy is the tridentate 2-(2-pyridylethyl)amino-3-butanone oxime ligand and LNHpy is its conjugate base, led to the formation of a new class of organocobalt complexes of general formula [RCo III (LNHpy)(HLNHpy)]-(ClO 4 ) [R = Me (2a), Et (2b), CH 2 CF 3 (2c), nBu (2d), and CH 2 Cl (2e)]. All the complexes were characterised by 1 H and 13 C NMR spectroscopy. The X-ray structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…205 Studies on bis(imino) pyridine-ligated cobalt ethylene polymerisation catalysts have strongly indicated that the activated species is not the anticipated cobalt() alkyl cation. 206 Tridentate amino-oxime ligands have been used to support new Co() alkyl derivatives such as 41; 207 Electroluminescent organometallic Ir complexes containing fluorinated and cyclometalated aryl-pyridine and related ligands are being developed as processable, tuneable, highly efficient electroluminescent materials. 210 A series of trans-Rh(allenylidene) 2 complexes 43 show an unprecedented type of migratory insertion reaction where the unsaturated C 3 unit migrates into the Rh-O and Rh-C bonds of cis ligands.…”
Section: Cobalt Rhodium and Iridiummentioning
confidence: 99%
“…205 Studies on bis(imino) pyridine-ligated cobalt ethylene polymerisation catalysts have strongly indicated that the activated species is not the anticipated cobalt() alkyl cation. 206 Tridentate amino-oxime ligands have been used to support new Co() alkyl derivatives such as 41; 207 Electroluminescent organometallic Ir complexes containing fluorinated and cyclometalated aryl-pyridine and related ligands are being developed as processable, tuneable, highly efficient electroluminescent materials. 210 A series of trans-Rh(allenylidene) 2 complexes 43 show an unprecedented type of migratory insertion reaction where the unsaturated C 3 unit migrates into the Rh-O and Rh-C bonds of cis ligands.…”
Section: Cobalt Rhodium and Iridiummentioning
confidence: 99%
“…have been extensively studied [38][39][40][41][42][43]. Binuclear complexes of 4-(2-amino-4-methylphenolisonitrosoacetyl)biphenyl were synthesized and characterized [42].…”
Section: Introductionmentioning
confidence: 99%
“…A useful model, which may be applied to study the trans effect in alkylcobalamins is represented by complexes of the type [Co(LNHpy)(HLNHpy)R] + (R = Et, Me, CF 3 CH 2 and bridging-CH 2 , HLNHpy = 2-(2-pyridylethyl)amino-3butanone oxime and LNHpy − its conjugate base). 26 In these models the pyridyl trans to the alkyl group, is covalently linked to the equatorial system by an ethylenic chain. It was found that the second order rate constants for the substitution of pyridyl by cyanide (a reaction reminiscent of the replacement of benzimidazole in cobalamins) are 19.1, 0.25, 2.2 × 10 −2 and 1.7 × 10 −2 M −1 s −1 for R = Et, Me, CF 3 CH 2 and bridging-CH 2 , respectively.…”
Section: Introductionmentioning
confidence: 99%